Characterization of microplastics found in the intertidal zones of Jericoacoara National Park, Ceará, Brazil - Araujo Dutra, Karina Aparecida; Camargo Maia, Rafaela (Arquivos de Ciências do Mar, 2023)
The present work evaluated the presence of microplastics at three points in the Parna de Jericoacoara, analyzing the beach sediment and four benthic species of sandstone reefs: the bivalve Brachidontes exustus, the gastropods Stramonita brasiliensis and Lottia subrugosa and the barnacles Chthamalus bisinuatus. The results obtained showed concentrations of microplastics, classified into fragments, fibers and pellets, from products for human use. Fragments were the most abundant polymers in the study and showed color diversity. Fiber was the only class found at all collection points and pellets were the least abundant in the study. It was also a black colored fiber in B. exustus and a blue colored fiber in C. bisinuatus. Fiffy-three point ninety-two percent of the microplastics found in the sediment had dimensions smaller than 1 mm. The data obtained in the present work indicate that microplastics are present in the beach area and in suspensory animals of Jericoacoara, requiring management and environmental education measures to help in the conservation of the Parna. Keywords: environmental impact, beach, conservation unit.